Circulating Levels of Interferon Regulatory Factor-5 Associates With Subgroups of Systemic Lupus Erythematosus Patients - Idborg, Helena; Zandian, Arash; Ossipova, Elena; Wigren, Edvard; Preger, Charlotta; Mobarrez, Fariborz; Checa, Antonio; Sohrabian, Azita; Pucholt, Pascal; Sandling, Johanna K.; Fernandes-Cerqueira, Cátia; Rönnelid, Johan; et al. (Frontiers in Immunology, 2019)
Systemic Lupus Erythematosus (SLE) is a heterogeneous autoimmune disease, which currently lacks specific diagnostic biomarkers. The diversity within the patients obstructs clinical trials but may also reflect differences in underlying pathogenesis. Our objective was to obtain protein profiles to identify potential general biomarkers of SLE and to determine molecular subgroups within SLE for patient stratification. Plasma samples from a cross-sectional study of well-characterized SLE patients (n=379) and matched population controls (n=316) were analyzed by antibody suspension bead array targeting 281 proteins. To investigate the differences between SLE and controls, Mann-Whitney U-test with Bonferroni correction, generalized linear modelling and receiver operating characteristics (ROC) analysis were performed. K-means clustering was used to identify molecular SLE subgroups. Interferon regulating factor 5 (IRF5) expressing microparticles were detected by flow cytometry to confirm the presence of IRF5 in plasma. Detection of extracellular IRF5 was further confirmed by immunoprecipitation-mass spectrometry (IP-MS). We identified IRF5, solute carrier family 22 member 2 (SLC22A2) and S100 calcium binding protein A12 (S100A12) as the three proteins with the largest fold change between SLE patients and controls (SLE/Control = 1.4, 1.4 and 1.2 respectively). The lowest p-values comparing SLE patients and controls were obtained for S100A12, Matrix metalloproteinase-1 (MMP1) and SLC22A2 (padjusted=3x10-9, 3x10-6 and 5x10-6 respectively). In a set of 15 potential biomarkers differentiating SLE patients and controls, two of the proteins were transcription factors, i.e., IRF5 and SAM pointed domain containing ETS transcription factor (SPDEF). IRF5 was up-regulated while SPDEF was found to be down-regulated in SLE patients. Unsupervised clustering of all investigated proteins identified three molecular subgroups among SLE patients, characterized by 1) high levels of rheumatoid factor-IgM, 2) low IRF5, and 3) high IRF5. Interestingly IRF5, a known genetic risk factor for SLE, was detected extracellularly and suggested by unsupervised clustering analysis to differentiate between SLE subgroups. Our results imply a set of circulating molecules as markers of possible pathogenic importance in SLE. We believe that these findings could be of relevance for understanding the pathogenesis and diversity of SLE, as well as for selection of patients in clinical trials.